Sistem Pengelolaan Sampah Berbasis Teknologi: Studi Desain Bak Sampah Otomatis Berbasis Arduino Sebagai Upaya Pengabdian Masyarakat - Suhartini; Amri Muliawan Nur; Julaini; Zainul Hadi (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The issue of waste has become one of the most important concerns worldwide, requiring serious attention from all segments of society. This is due to the increasing volume of waste along with the growing population. Many villages face major problems in terms of ineffective waste management systems and the low public awareness regarding waste management, especially in the Surabaya Village Office, East Lombok Regency, which negatively impacts health and the comfort of public spaces. The Surabaya Village Office, as a public service center, plays an important role in creating a clean, healthy, conducive, and productive work environment. An effort to modernize conventional waste management in the Surabaya Village Office is by designing an automatic trash bin system based on Arduino using ultrasonic sensors to automatically open and close the trash bin. This aims to avoid direct physical contact and unpleasant odors. The utilization of Arduino technology provides an innovative solution for waste management. The results of the innovation in making an automatic trash bin using Arduino can improve the effectiveness and efficiency of waste management in the Surabaya Village Office